Nanometer-sized domains in Langmuir-Blodgett films for patterning SiO2 - Kataoka, Sho (Langmuir : the ACS journal of surfaces and colloids, 2010)
In this study, we prepared Langmuir-Blodgett films with domains ranging from 20 to 100 nm in size by using perfluorinated fatty acids. The domain size of the obtained LB films is markedly smaller than the ordinary domain size of hydrocarbons and fluorocarbons on the micrometer scale. The domains were prepared by controlling their growth through the addition of 2-propanol to the subphase of Langmuir monolayers. Furthermore, the prepared domains in the LB films were used as templates for patterning SiO(2) films. The obtained SiO(2) films have completely negative structures compared with those of the domains in the LB films